2004
DOI: 10.1111/j.1365-2052.2004.01154.x
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion ofgalectin 9as a candidate gene for hyperuricosuria in the Dalmatian dog

Abstract: All Dalmatian dogs have an inherited defect in purine metabolism leading to high levels of uric acid excretion in their urine (hyperuricosuria) rather than allantoin, the normal end product of purine metabolism in all other breeds of dog. Transplantation experiments have demonstrated that the defect is intrinsic to the liver and not the kidney. Uricase, the enzyme involved in the breakdown of urate into allantoin, has been shown to function in Dalmatian liver cells. Therefore, candidate genes for this defect i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In the cell-cell communication analysis, we found that the activity of the GALECTIN signaling pathway was overexpressed in model 2 and the increase of T cell-mediated intercellular communication. Galectin-9 is a sugar-regulated urate transporter/channel [78], and the exclusion of galectin-9 as a candidate gene may cause hyperuricosuria in dalmatian dogs [79]. Galectin-9 regulates monosodium urate crystalinduced gouty in ammation through the modulation of the Treg/Th17 ratio…”
Section: Discussionmentioning
confidence: 99%
“…In the cell-cell communication analysis, we found that the activity of the GALECTIN signaling pathway was overexpressed in model 2 and the increase of T cell-mediated intercellular communication. Galectin-9 is a sugar-regulated urate transporter/channel [78], and the exclusion of galectin-9 as a candidate gene may cause hyperuricosuria in dalmatian dogs [79]. Galectin-9 regulates monosodium urate crystalinduced gouty in ammation through the modulation of the Treg/Th17 ratio…”
Section: Discussionmentioning
confidence: 99%
“…Amplified products were run on an ABI Prism 3100 Genetic Analyzer (Applied Biosystems) and analysed by STR and software 5 . Canine microsatellites included FH2712 6 , ura104.4 7 and a Y chromosome microsatellite, 650‐79.2 8 . Previously unpublished primer sequences are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%